2021
DOI: 10.3748/wjg.v27.i41.7159
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term outcomes of laparoscopic vs open ileocolic resection in patients with Crohn's disease: Propensity-score matching analysis

Abstract: BACKGROUND Laparoscopic ileocolic resection (LICR) is the preferred surgical approach for primary ileocolic Crohn’s disease (CD) because it has greater recovery benefits than open ICR (OICR). AIM To compare short- and long-term outcomes in patients who underwent LICR and OICR. METHODS Patients who underwent ICR for primary CD from 2006 to 2017 at a single tertiary center specializing in CD were included. Patients who underwent LICR and OICR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Our study also observed reduced hospital admission costs when MIS was used. MIS utilization for IBD-related surgery has been associated with reductions in complication rates and length of hospital stay, as well as reduced rates of reoperation or readmission [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also observed reduced hospital admission costs when MIS was used. MIS utilization for IBD-related surgery has been associated with reductions in complication rates and length of hospital stay, as well as reduced rates of reoperation or readmission [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also observed reduced hospital admission costs when MIS was used. MIS utilization for IBD‐related surgery has been associated with reductions in complication rates and length of hospital stay, as well as reduced rates of reoperation or readmission [16–18]. Due to these benefits, reduced access to this surgical approach among uninsured or publicly insured IBD patients may further increase their risk of financial toxicity after IBD‐related surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable debate in the literature about use of MIS for CD for many different reasons, but as with many other conditions, when laparoscopic techniques have been used in Crohn’s disease surgery in adults and children, they have been shown to result in shorter hospital stays, faster return to a regular diet, less postoperative narcotic use, and better cosmetic results [ 14 , 23 , 32 ]. These results have been confirmed also in our analysis—postoperative oral intake was started significantly earlier in patients in LG than in OG (LG 1 days versus OG 3 days, p < 0.0001) as well as central venous catheter ( p < 0.0001), parenteral nutrition ( p < 0.0001), postoperative urinary cathetrisation ( p < 0.0001) and need of epidural analgesia ( p = 0.009) were shorter in LG, the length of hospitalisation was also significantly shorter in LG ( p = 0.0005).…”
Section: Discussionmentioning
confidence: 99%
“…While some surgeries, such as thoracotomy, mastectomy, or amputations, are considered with a higher risk for the development of CPSP compared to other surgical procedures, the data on prevalence are highly variable. The evidence on a protective effect of laparoscopic versus open surgery is not consistent [13,[126][127][128][129]. The influence of intraoperative factors, such as the duration of surgery or the surgical technique, in terms of extent of nerve damage and invasiveness (e.g.…”
Section: Risk Factors Related To Surgical Procedures and Pain Managementmentioning
confidence: 99%